Expression and purification of the recombinant mouse tumor supressor cytochrome b561 protein - Bérczi, Alajos; Asard, Han (Acta Biologica Szegediensis, 2008)
It has recently been recognized that ascorbate-reducible cytochrome b561 (Cyt-b561) proteins constitute a well-distinguished protein family amongst the two-heme containing b-type cytochromes, ubiquitously present in animals and plants. Of the six isoforms that have been identified in mammals, three isoformes (called CGCytb, DCytb, and LCytb) have been cloned and expressed in yeast and/or bacterial cells. The recombinant proteins have been characterized in some detail. A particular gene product of the 3p21.3 (human) and 9F1 (mouse) chromosomal region, a so-called tumor supressor protein (101F6, TSP10), was identified as a Cyt-b561 protein by sequence homology. We have cloned and expressed the mouse tumor supressor Cyt-b561 protein (TSCytb) in yeast (Saccharomyces serevisiae), without and with a His6-tag on either the N- or the C-terminus. The C-terminal His6-tagged recombinant protein was purified on Ni-NTA His•Bind resin to almost homogeneity. Using optical spectroscopy we show that TSCytb is indeed an ASC-reducible cytochrome b561 protein and that ASC-reducibility is not affected by the presence of a His6-tag on the C-terminus. Minor differences in the properties of TSCytb and the other three mammalian Cyts-b561 are discussed.